Automation of an Interferon-γ Release Assay and Comparison to the Tuberculin Skin Test for Screening Basic Military Trainees for Mycobacterium tuberculosis Infection. Issue 3 (1st March 2014) - Goodwin, Donald J.; Mazurek, Gerald H.; Campbell, Brandon H.; Bohanon, Jamaria; West, Kevin B.; Bell, James J.; Powell, Richard; Toney, Sean; Morris, John A.; Yamane, Grover K.; Sjoberg, Paul A.
ABSTRACT: We automated portions of the QuantiFERON-TB Gold In-Tube test (QFT-GIT) and assessed its quality when performed concurrently with the tuberculin skin test (TST) among U.S. Air Force basic military trainees (BMTs). The volume of blood collected for QFT-GIT was monitored. At least one of the three tubes required for QFT-GIT had blood volume outside the recommended 0.8- to 1.2-mL range for 688 (29.0%) of 2, 373 subjects who had their blood collected. Of the 2, 124 subjects who had TST and QFT-GIT completed, TST was positive for 0.6%; QFT-GIT was positive for 0.3% and indeterminate for 2.0%. Among 2, 081 subjects with completed TST and determinate QFT-GIT results, overall agreement was 99.5% but positive agreement was 5.6%. Specificity among the 1, 546 low-risk BMTs was identical (99.7%). Indeterminate QFT-GIT results were 2.7 times more likely when mitogen tubes contained >1.2 mL blood than when containing 0.8- to 1.2-mL blood. Automation can facilitate QFT-GIT completion, especially if the recommended volume of blood is collected. Mycobacterium tuberculosis infection prevalence among BMTs based on TST and QFT-GIT is similar and low. Selectively testing those with significant risk may be more appropriate than universal testing of all recruits.